The Labor Contract Law and the Digital Transformation of Enterprises – Analysis based on Dual Perspective of Quantity and Quality of Employees - Xu, Xinyue (Transactions on Economics, Business and Management Research, 2024)
The labor protection of employees caused by the Labor Contract Law has attracted wide attention, affecting the employment and even business activities of enterprises. Using the data of listed companies from 2005 to 2013, we aim to research the impact of the Labor Contract Law on digital transformation of enterprises. The results show that the Labor Contract Law has positive impact on enterprises’ digital transformation, and this conclusion is still valid after a series of robustness tests. The promotion effect of Labor Contract Law on enterprises’ digital transformation is more significant in state-owned enterprises and enterprises in areas with better legal environment. Mechanism analysis shows that the Labor Contract Law promotes digital transformation activities through improving the quality of employees and reducing the number of employees. The above conclusions are consistent with the logic that enterprises want to avoid high labor costs by reducing costs and increasing efficiency, and then promote the digital transformation. We believe that this paper will have significance to improve the legal system of the labor market and guide enterprises to improve digitization.